Screening and the Detection of Gonorrhea - Holmes, King K. (1975)
The purpose of a physician's screening for gonorrhea is the provision of comprehensive health care to patients who seek his care. Among sexually active young patients, gonorrhea is probably far more common than many other diseases a physician “screens” for during a routine physical examination. Since gonorrhea culture tests are too costly in time and money to be offered to every patient, guidelines can be used to select patients for screening who are most likely to have gonorrhea. The gonorrhea culture test should be carried out in the same spirit as a cervical cytology test, as a potential health benefit and without stigma. However, even more important than gonorrhea screening, from the standpoint of the patient, is (1) increased use of culture for diagnostic problem solving, particularly in women with dysuria, abnormal vaginal discharge, abnormal menstrual bleeding or lower abdominal pain, and (2) location and treatment of sex partners.